Codoping Effect of Nitrogen (N) to Iron (Fe) Doped Zirconium Titanate (ZrTiO4) Composite toward Its Visible Light Responsiveness as Photocatalysts - Rizka Hayati; Rian Kurniawan; Niko Prasetyo; Sri Sudiono; Akhmad Syoufian (Universitas Gadjah Mada, 2022)
Iron (Fe) and nitrogen (N) were introduced as dopants into zirconium titanate (ZrTiO4) in order to study the codoping effects of nitrogen on iron-doped zirconium titanate (Fe,N-codoped ZrTiO4) composite. Titanium tetraisopropoxide (TTIP), zirconia (ZrO2), urea, and iron(II) sulfate heptahydrate were used as the source of TiO2, semiconductor supports, source of nitrogen, and iron, respectively. A specific amount of iron (1, 3, 5, 7, and 9 wt.%) and a fixed nitrogen content (10 wt.%) were doped into the ZrTiO4 lattice. Various calcination temperatures (from 500 to 900 °C) were also applied to investigate the crystal structure of the composite. The composites were characterized by X-ray powder diffractometer (XRD), Fourier-transform infrared spectrophotometer (FT-IR), scanning electron microscope with energy dispersive X-Ray spectrometer (SEM-EDX), and specular reflectance UV-Vis (SR-UV). The lowest bandgap energy of 2.62 eV was obtained in the composite with 3 wt.% of Fe and 10 wt.% of N calcined at 500 °C.